Chimeric Antigen Receptor T-Cell Therapy of Neurolymphomatosis Monitored by FDG PET/CT. (31st May 2023) - Li, Siqi; Wang, Hongrong; Wang, Guanyun; Lu, Xia; Yang, Jigang
Abstract: 18 F-FDG PET/CT was performed to evaluate possible recurrent B-cell lymphoblastic lymphoma in a 34-year-old man. The images showed multiple foci of increased activity in the nerve root and peripheral nerve. A biopsy confirmed the diagnosis of neurolymphomatosis. After receiving chemotherapy, PET/CT showed progressive disease. The patient subsequently received the CD-19 chimeric antigen receptor T-cell therapy. A follow-up PET/CT acquired 30 days after chimeric antigen receptor T-cell therapy revealed no abnormal FDG activity.